2017
DOI: 10.1038/s41598-017-00714-7
|View full text |Cite
|
Sign up to set email alerts
|

A Pair of Maternal Chromosomes Derived from Meiotic Nondisjunction in Trisomy 21 Affects Nuclear Architecture and Transcriptional Regulation

Abstract: Eukaryotic genomes are organised into complex higher-order structures within the nucleus, and the three-dimensional arrangement of chromosomes is functionally important for global gene regulation. The existence of supernumerary chromosome 21 in Down syndrome may perturb the nuclear architecture at different levels, which is normally optimised to maintain the physiological balance of gene expression. However, it has not been clearly elucidated whether and how aberrant configuration of chromosomes affects gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…We previously generated a patient-derived Tri21 iPSC line that contains one paternal copy and two maternal copies of chromosome 21 22 . Using this DS-speci c iPSC line, we further generated a corrected disomy 21 iPSC line (cDi21 iPSC), in which a single copy of chromosome 21 was arti cially removed from a Tri21 iPSC line 23 , and a partial trisomy 21 iPSC line (Partial-Tri21 iPSC) in which a 4-megabase (Mb) region corresponding to a 'Down syndrome critical region' was selectively deleted only from the paternal chromosome 21 in Tri21 iPSCs (Fig. 1) 22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously generated a patient-derived Tri21 iPSC line that contains one paternal copy and two maternal copies of chromosome 21 22 . Using this DS-speci c iPSC line, we further generated a corrected disomy 21 iPSC line (cDi21 iPSC), in which a single copy of chromosome 21 was arti cially removed from a Tri21 iPSC line 23 , and a partial trisomy 21 iPSC line (Partial-Tri21 iPSC) in which a 4-megabase (Mb) region corresponding to a 'Down syndrome critical region' was selectively deleted only from the paternal chromosome 21 in Tri21 iPSCs (Fig. 1) 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Gene-rich chromosomes are located preferentially at the centre of the nucleus, whereas gene-poor chromosomes, such as chromosome 18, are located at its periphery 46 . Cell-type-speci c interaction patterns among chromosome territories are correlated with genome regulation at the global level, and the presence of a supernumerary chromosome 21 may perturb the physiological positioning of other chromosomes in the nucleus, leading to transcriptional dysregulation 23,47 . XIST-mediated silencing of extra chromosome 21 reverted trisomy-induced transcriptional changes in other chromosomes, leading to downregulated expression levels, which was less noticeable but became evident by comparing the isogenic cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3d,e). To exclude the possible effects of genetic variability, this result was validated in another experiment using isogenic control cell lines: a corrected disomy 21 (cDi21) iPSC line, in which a single copy of chromosome 21 was removed from a Tri21 iPSC 29 , and a rescued disomy 13 (rDi13) iPSC line, in which a copy of chromosome 13 was spontaneously elimi- Abnormally high accumulation of protein aggregates containing non-specific proteins in trisomic neurons. We next evaluated the accumulation of protein aggregates in NGN2-neurons and found that aggregates containing p62 were significantly increased in trisomic neurons compared with diploid neurons (Fig.…”
Section: Impaired Cell Viability and Elevated Apoptotic Cell Death Inmentioning
confidence: 99%
“…A single loxP site contains two 13-bp inverted repeats flanking an asymmetric 8-bp core sequence recognized by Cre recombinase [90]. Integration of the inverted loxP into the chromosomes were performed by conventional gene targeting, CRISPR/Cas9 nickase system, and TALEN technology, respectively [82,83,91]. Chromosomes with inverted loxP sites can be converted to unstable dicentric and acentric chromosomes in a Cre recombinase-dependent manner (Figure 1).…”
Section: Cre/loxp System-mediated Chromosome Eliminationmentioning
confidence: 99%